Empirical Attenuation relationship for Peak Ground Horizontal Acceleration for North-East Himalaya - Kumar*, Arjun; Mittal, Himanshu; Kumar, Rohtash; Ahluwalia, Rajeev Saran (Vietnam Journal of Earth Sciences, 2017)
North-East India is located in one of the most seismic prone areas of the world. India has faced several devastating earthquakes in the past. The largest of these have originated in the Himalayan plate boundary region, which has remained a region of great scientific and engineering interest. In spite of this, very little seismological information is available about North- East India, which is the focus for present study. Only few attenuation relationships are available for this region, which are most valuable in a region where too much strong motion recordings are not available. However in recent time, with the inception of 300 strong motion instruments under Indian National Strong Motion Network deployed under Mission Mode project (Government of India), a good quality of strong motion data became available. Taking the advantage of data collected by this network and earlier analogue strong motion arrays, an endeavor has been made to develop an empirical attenuation relationship for peak horizontal ground accelerations for North-East Himalayan region in India. The data set consists of 216 peak ground horizontal accelerations from 24 earthquakes (4.0≤M≤6.8) recorded by strong-motion arrays and National Strong Motion Network project in India. The present analysis uses a two-step stratified regression model. The estimated attenuation relationship for the region is\(\log(A) = -1.097 + 0.3882M - 1.19\log(X+e^{0.2876M})\)Where A is the peak ground acceleration (g), M is the magnitude, and X is the hypocentral distance from the source. The residual sum of squares is 0.1451. The obtained Empirical attenuation relationship will provide better insight for site specific studies as well as for hazard estimation for North-East Himalayan region. Attenuation relationships for expected peak ground acceleration (g) have been presented for magnitudes 5, 6, 7 and 8 for North-East Himalayan region.References Abrahamson, N.A., Litchiser, J.J., 1989. Attenuation of vertical peak accelerations. Bulletin of the Seismological Society of America, 79, 549-580. Aman, A, Singh, U.K., Singh,  R.P., 1995. A new empirical relation for strong seismic ground motion for the Himalayan region. Current Science, 69(9), 772-777. Ambraseys, N.N., Douglas, J., 2003. Near-field horizontal and vertical earthquake ground motions. Soil Dynamics and Earthquake Engineering, 23, 1-18. Atkinson, G.M., Boore, D.M., 2003. Empirical ground-motion relations for subduction zone earthquakes and their application to Cascadia and other regions. Bulletin of the Seismological Society of America, 93, 1703-1729. Ben-Menahem, A., Aboudi, E., Schild, R., 1974. The source of the great Assam earthquake-an intraplate wedge motion. Physics of Earth and Planetary Interior, 9, 265-289. Bilham, R., England, P., 2001. Plateau ‘pop up’ in the great 1897 Assam earthquake. Nature, 410, 806-809. Boore, D.M., Joyner, W.B., 1982. The empirical prediction of ground motion. Bulletin of the Seismological Society of America, 72, 843-860. Campbell, K.W., 1985. Strong motion attenuation relations: a ten year perspective. Earthquake Spectra, 1, 759-803. Campbell, K.W., Bozorgnia, Y., 2003. Updated near-source ground-motion  (attenuation) relations for the horizontal and vertical components of peak ground acceleration and acceleration response spectra. Bulletin of the Seismological Society of America, 93, 314-331. Chandrasekaran, A.R., Das, J.D., 1991. Analysis of strong ground motion accelerograms of Uttarkashi Earthquake of October 20. Department of Earthquake Engineering, Univversity of Roorkee, India Report, EQ: 91-10. Chandrasekaran, A.R.,  Das, J.D., 1992. Strong motion arrays in India and analysis of data from Shillong array, Current Science, 62, 233-250. Dewey, J.F., Bird, J.M., 1970. Mountain belts and the new global tectonics. Journal of Geophysical Research, 75, 2625-2647. Douglas, J., 2001. A comprehensive worldwide summary of strong-motion attenuation relationships for peak ground acceleration and spectral ordinates (1969 - 2000). ESEE Report 01-1, Department of Civil and Environmental Engineering, Imperial College, London. Fukushima, Y., Tanaka, T., 1990. A new attenuation relation for peak horizontal acceleration of strong earthquake ground motion in Japan. Bulletin of the Seismological Society of America, 80, 757-783. Fukushima, Y., Berge-Thierry, C., Volant, P., Griot-Pommera, D.A., Cotton, F., 2003. Attenuation relation for West Eurasia determined with recent near-fault records from California, Japan and Turkey. Journal of Earthquake Engineering, 7(4), 573-598. IS1893 (Part 1) 2002. Indian standard criteria for earthquake resistant design of structures, part 1, general provisions and buildings (Fifth Revision). Bureau of Indian Standards, New Delhi 110002, 42. Iyengar, R.N., Ghosh, S., 2004. Microzonation of earthquake hazard in Greater Delhi area; Current Science, 87, 1193-1202. Jain, S.K., Roshan, A.D., Arlekar, J.N.,  Basu, P.C., 2000. Empirical attenuation relationships for the Himalayan earthquakes based on Indian strong motion data. Proceedings of the Sixth International Conference on Seismic Zonation. Joyner, W.B., Boore, D.M., 1988. Measurement, characterisation, and prediction of strong ground motion. Proceeding of Earthquake Engineering and Soil Dynamics I1 GT Div/ASCE, Utah, 43-102. Kayal, J.R., 1987. Microseismicity and source mechanism study: Shillong Plateau, Northeast India. Bulletin of the Seismological Society of America, 77, 184-194. Kayal, J.R., 1996. Earthquake source processes in northeast India: a review. Journal of Himalayan Geology, 17, 53-69. Kayal, J. R., 1998. Seismicity of northeast India and surroundings-development over the past 100 years. Journal of Geophysics, XIX, 9-34. Khattri, K.N., Rogers, A.M., Perkins, D.M, Algermissen, S.T., 1984. A seismic hazard map of India and adjacent areas. Tectonophysics, 108, 93-134. Kramer, S. L., 1996. Geotechnical earthquake engineering. Pearson Education India. Kumar, A., Mittal, H., Sachdeva, R., Kumar, A., 2012. Indian strong motion instrumentation network. Seismological Research Letters, 83(1), 59-66. Kumar, A., Kumar, A., Mittal, H., Kumar, A., Bhardwaj, R., 2012. Software to Estimate Earthquake Spectral and Source Parameters. International Journal of Geosciences, 3(5), 1142-1149. Kumar, A., Kumar, A., Gupta, S.C., Mittal, H., Kumar, R., 2013a. Source parameters and fmax in Kameng region of Arunachal Lesser Himalaya. Journal of Asian Earth Sciences, 70-71, 35-44. Kumar, R., Gupta, S.C., Kumar, A., Mittal, H., 2013b. Source parameters and fmax in lower Siang region of Arunachal lesser Himalaya. Arabian Journal of Geosciences, DOI 10.1007/s12517-013-1223-8. Mittal, H., Kumar, A., Ramhmachhuani, R., 2012. Indian National Strong Motion Instrumentation Network and Site Characterization of Its Stations. International Journal of Geosciences, 3(6), 1151-1167. Mukhopadhyay, M., 1984. Seismotectonics of transverse lineaments in the eastern Himalaya and foredeep, Tectonophysics, 109, 227-240. Nandy, D.R., 2001. Geodynamics of northeastern India and the adjoining region. acb Publication, Calcutta. Nath, S.K., Thingbaijam, K.K.S., Maiti, S.K., Nayak, A., 2012. Ground-motion predictions in Shillong region, northeast India. Journal of Seismology, 16(3), 475-488. Parvez, I.A., Sutar, A.K., Mridula, M., Mishra, S.K., Rai, S.S., 2008. Coda Q estimates in the Andaman Islands using local earthquakes. Pure and Applied Geophysics, 165(9-10), 1861-1878. Raghukanth, S.T.G., Kavitha, B., 2014. Ground motion relations for active regions in India. Pure and Applied Geophysics, 171(9), 2241-2275. Sharma, M.L., 1998. Attenuation relationship for estimation of peak ground horizontal acceleration using data from Strong-Motion Arrays in India. Bulletin of the Seismological Society of America, 88(4), 1063-1069. Sharma, M.L., 2005. A new empirical attenuation relationship for peak ground horizontal acceleration for Himalayan region using Indian and worldwide data set. Journal of Geophysics, 26(3), 151-158. Singh, R.P., Aman, A., Prasad, Y.J.J., 1996. Attenuation relations for strong seismic ground motion in the Himalayan region. Pure and Applied Geophysics, 147(1), 161-180. Sun, F., Peng, K., 1993. Attenuation of strong ground motion in western U.S.A. Earthquake Research in China, 7(1), 119-131. Thingbaijam, K.K.S., Nath, S.K., Yadav, A., Raj, A., Walling, M.Y., Mohanty, W.K., 2008. Recent seismicity in northeast India and its adjoining region. Journal of Seismology, 12(1), 107-123. Trifunac, M.D., 1976. Preliminary analysis of the peaks of strong earthquake ground motion - dependence of peaks on earthquake magnitude, epicentral distance, and recording site conditions. Bulletin of the Seismological Society of America, 66(1), 189-219. Verma, R.K., Mukhopadhyay, M., Ahluwalia, M.S., 1976. Seismicity, gravity and tectonics of Northeast India and Northern Burma. Bulletin of the Seismological Society of America, 66, 1683-1694.